Dosimetric features and kinetic parameters of a glass system dosimeter. (28th December 2019) - Mhareb, M.H.A.; Alajerami, Y.S.M.; Alqahtani, Muna; Alshahri, Fatimh; Saleh, Noha; Alonizan, N.; Maghrabi, M.; Hashim, S.; Ghoshal, S.K.
Abstract: Lithium borate (LB) glasses doped with dysprosium oxide (Dy2 O3 ) have been prepared by utilizing the conventional melt‐quench technique. The prepared glass samples were exposed to 60 Co to check their dosimetric features and kinetic parameters. These features involve glow curves, annealing, fading, reproducibility, minimum detectable dose (MDD), and effective atomic number ( Z eff ). Kinetic parameters including the frequency factors and activation energy were also determined using three methods (glow curve analysis, initial rise, and peak shape method) and were thoroughly interpreted. In addition, the incorporation of Dy impurities into LB enhanced the thermoluminescence sensitivity 170 times. The glow from LB:Dy appeared as a single prominent peak at 190°C. The best annealing proceeding was obtained at 300°C for 30 min. Signal stability was reported for a period of 1 and 3 months with a reduction of 26% and 31%, respectively. The proposed glass samples showed promising dosimeter properties that can be recommended for personal radiation monitoring.